PLANNING OF ROUNDS OF SETTLEMENTS TAKING INTO ACCOUNT THE MODES MOTIONS OF TRANSPORT STREAMS - Угненко, Є.; Бєлятинський, А.; Ужвієва, О. (Proceedings of National Aviation University, 2012)
Reduction of negative influence is the purpose of work on the settlements of transit cars – building of roundabout roads (difficult engineering buildings) which allow decreasing the anthropogenic influencing of highway